MODERN TENDENCIES OF TOURISTIC DEMAND - I.V. POPOVA (Advanced Engineering Research)
Tourism as a kind of activity is directed for rendering of various kinds of services and goods of touristic demand by touristic enterprises for the purpose of assisting satisfaction of various cultural, spiritual, cognitive and other touristic needs. The article covers disclosure of modern tendencies on market of touristic ser- vices which are predetermined by interests and solvency of different groups of people.